2016
DOI: 10.1039/c6cp03102a
|View full text |Cite
|
Sign up to set email alerts
|

Realizing controllable graphene nucleation by regulating the competition of hydrogen and oxygen during chemical vapor deposition heating

Abstract: Oxygen can passivate Cu surface active sites when graphene nucleates. Thus, the nucleation density is decreased. The CuO/Cu substrate was chosen for graphene domain synthesis in our study. The results indicate that the CuO/Cu substrate is beneficial for large-scale, single-crystal graphene domain synthesis. Graphene grown on the CuO/Cu substrate exhibits fewer nucleation sites than on Cu foils, suggesting that graphene follows an oxygen-dominating growth. Hydrogen treatment via a heating process could weaken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It was shown that the flake nucleation suppression during CVD growth is observed if the Cu oxide still exists on the Cu foil during sample annealing until the temperature is reached where oxygen diffusion into the Cu bulk sets in. In this case the dissolved oxygen inside the Cu foil can act as an oxygen reservoir until the CVD process is started . It was also shown recently that stabilizing the Cu 2 O layer on the Cu foil up to the even higher temperature of 1050°C in oxygen followed by the sudden reduction in a hydrogen atmosphere leads to an irreversible conversion of the polycrystalline Cu towards a Cu(111) crystallized foil …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was shown that the flake nucleation suppression during CVD growth is observed if the Cu oxide still exists on the Cu foil during sample annealing until the temperature is reached where oxygen diffusion into the Cu bulk sets in. In this case the dissolved oxygen inside the Cu foil can act as an oxygen reservoir until the CVD process is started . It was also shown recently that stabilizing the Cu 2 O layer on the Cu foil up to the even higher temperature of 1050°C in oxygen followed by the sudden reduction in a hydrogen atmosphere leads to an irreversible conversion of the polycrystalline Cu towards a Cu(111) crystallized foil …”
Section: Resultsmentioning
confidence: 98%
“…the treatment also leads to a passivated surface during the initial stage of the CVD process, since Cu‐oxide is catalytically less active than the metallic Cu surface, although it has later been shown that graphene can be also grown on oxidized Cu in a pure CH 4 stream . Meanwhile, further studies proved that graphene flake nucleation during CVD can be effectively suppressed, when using Cu foils that have been oxidized before insertion into the reactor . It was shown that the flake nucleation suppression during CVD growth is observed if the Cu oxide still exists on the Cu foil during sample annealing until the temperature is reached where oxygen diffusion into the Cu bulk sets in.…”
Section: Resultsmentioning
confidence: 99%
“…And excess hydrogen could etch graphene to destroy the integrity of the lattice and make the quality of graphene worse [64]. It also affects the adsorption, stability, thickness [65][66][67], population of active species on the catalyst surface [68,69] and the morphology [70][71][72][73][74][75][76][77][78][79] of the grown graphene. Luo et al [72] determined the effect of hydrogen on the shape and orientation of graphene using DFT calculation (shown in Figure 7).…”
Section: Effect Of Hydrogenmentioning
confidence: 99%
“…Suzuki et al [74] detailed a threefold atmospheric pressure CVD process that removes traces of Si impurities originating from the furnace and promotes the formation of wider terraces on Cu foils without having to change the CVD growth parameters. Zhang et al developed a method for controlling the nucleation process on a CuO substrate by regulating the hydrogen flow in the furnace [75]. It has also been reported that oxygen can form oxide nucleation sites for graphene growth under high hydrogen partial pressures to produce single-layer graphene [76,77].…”
Section: Surface Morphologymentioning
confidence: 99%